ANALYSIS OF THE PHYSICAL AND PSYCHOLOGICAL PROFILE OF THE SCHOOL POPULATION OF THE CENTRAL DISTRICT OF HEREDIA, COSTA RICA - Herrera-González, Emmanuel (2017)
The purpose of this study was to establish a physical and psychological profile of fourth, fifth, and six graders. The study included a total of 1080 participants, specifically 318 fourth graders, 418 fifth graders and 344 sixth gradersbetween the ages of 9-15 years (mean age 11.10 ± 1.07). Size and weight were measured to establish BMI. Two self-report instruments were used to establish levels of physical activity: Pictorial Questionnaire of Children’s Physical Activity and Physical Activity Questionnaire for Older Boys and Girls. The PACER (Progressive Aerobic Cardiovascular Endurance Run) Test evaluates children and teenagers’ fitness level. Psychological variables were studied using the BIA Questionnaire and Lawrence’s Self-Esteem Questionnaire (LAWSEQ). According to the classification by the Center for Disease Control and Prevention (CDC), the level of overweight and obesity is 28.8% while the level of underweight is 4%. As for aerobic capacity (VO2max) 77.7% is in a healthy level for their age. Boyssee themselves more physically active than girls see themselves.Regarding self-esteem, 35% show low levels and only 10% have high self-esteem. As far as body image, the tendency of the ideal and future image is to be thinner.These results serve as a fundamental scientific basis for future research aimedat improving the health and well-being of the school population, taking into account the relationship between body image and children’s psychological aspects.